Relato de uma experiência junto a graduandos de pedagogia e avaliação do conhecimento por eles adquirido após uma atividade de educação ambiental sobre manguezais - João, Marcio Camargo Araujo [UNESP]; Talamoni, Ana Carolina Biscalquini [UNESP]; Pimenta, Camila Evelyn Rodrigues [UNESP]; Luiz, Victor dos Santos [UNESP]; Pinheiro, Marcelo Antonio Amaro [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The present study aims report an Environmental Education (EE) experience on mangroves and assess the knowledge acquired by academics in Pedagogy participating in such activity. A semistructured questionnaire was applied with three questions to 66 students from first to fourth year of this undergraduate course at an university located in the central coast of the State of São Paulo. The three questions were evaluated of qualiquantitative way. The first question (“What’s mangrove?”) features four categories to be defined (an ecosystem; transition environmental; suffers action of tides; and animal nursery), and 39.4% of people didn’t mention any of the required categories. The second question (“What are animals can be found in the mangrove?”) features five categories (mammals; fish; reptiles; birds; and invertebrates), and 37.9% of people mentioned two categories. The third question (“As the theme “crab” can be treated in a classroom for elementary school students?”) was open and all information was considered and categorized, with the category “Lectures” most cited (26.4%). The results in vast majority showed low knowledge acquired by students after the activity, which shows the need for innovations in the techniques for better efficiency and integration of the population to the mangrove ecosystem.

O presente trabalho tem por objetivo relatar a aplicação de uma atividade de Educação Ambiental (EA) sobre manguezais para acadêmicos de Pedagogia, além de avaliar os conhecimentos adquiridos por estes alunos. Um questionário semiestruturado com três questões foi aplicado para 66 alunos de primeiro à quarto anos do Curso de Pedagogia, de uma universidade localizada no Litoral Centro do Estado de São Paulo. As questões foram avaliadas de forma quali-quantitativa. A questão 1 (“O que é manguezal?”) apresentou quatro categorias de definição (um ecossistema; ambiente de transição; sofre ação de marés; e berçário animal), com 39,4% das pessoas não se enquadrando a nenhuma dessas categorias. A questão 2 (“Quais animais podem ser encontrados no manguezal?”) apresentou cinco categorias (mamíferos; peixes; répteis; aves; e invertebrados), com e 37,9% das pessoas citando duas delas. A questão 3 (“Como o tema caranguejo pode ser tratado em uma sala de aula para alunos do Ensino Fundamental I?”), por ser aberta, teve todas as informações avaliadas e categorizadas, sendo a categoria “Aulas Teóricas” a mais citada (26,4%). Grande parte dos resultados demonstra o reduzido conhecimento adquirido pelos alunos após a atividade, implicando na necessidade de inovações nas técnicas utilizadas, visando melhor eficácia e integração da população com o ecossistema manguezal.
Keywords: Environmental education; Mangrove; University extension; Educação ambiental; Manguezal; Extensão universitária